Figurative Language in Two Translated Chapters from Nietzsche's novel Zarathustra: A Stylistic Approach - Lubis , Fauziah Khairani; Suryanti Tambunan, Anna Riana; Andayani , Widya; Manullang , Elisa Betty; Damanik , Sisila Fitriany (International Journal of Language and Literary Studies, 2020)
This study aims to examine the figurative language used in two translated chapters taken from Friedrich Nietzsche's novel, Zarathustra. The two chapters chosen are namely Kebajikan yang Mengecilkan and Tiga Hal yang Jahat. This is a qualitative research which involves the stylistic approach in order to bring out the stylistic devices used in the chosen chapters; simile and personification. The data of this study were collected from the two translated chapters of the novel. In this study, it is found that a total of nine figures of speech were investigated: seven figures of simile and two other figures of personification respectively. The results of this study revealed that the simile device focused on illustrating the author's visual reality for the readers about the protagonist's situations, life-story, and imagination. On the other hand, the personification device illustrated the protagonist's visual aspects, ideas, and imagination which are very analogous to the author's perspective.